The Naturalization of Gender Segregation in a Danish Bank - Grosen, Sidsel Lond; Holt, Helle; Lund, Henrik L. (Nordic Journal of Working Life Studies, 2012)
Through a qualitative interview analysis of a document handling department in a Danish bank, this article seeks to illuminate central aspects of how some jobs come to be seen as naturally female. Taking gendered organizational theory and Joan Acker’s concept of an ideal employee as our point of departure, we ask whether women are seen as the ideal employees in this femaledominated job function or as a residual to men as the actual ideal employees. The numerical female dominance in the document handling department is articulated as a matter of competencies, job content, and family obligations – for example, by framing women as good at multitasking, as enjoying routine work, and as primary caregivers. The article argues that this construction both draws on and alters historically formed stereotypes in ways that reinforce the gender segregation of the organization and make it hard to change.